1994
DOI: 10.1007/bf00150343
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation of wheat by VA-mycorrhizal fungi was found to be higher on a farm managed in an organic manner than on a conventional neighbour

Abstract: Levels of colonisation by vesicular-arbuscular (VA)-mycorrhizal fungi were compared between adjacent farms, one operated in a conventional manner and the other run according to organic farming principles. Wheat grown on the organic farm was found to have VA-mycorrhizal colonisation levels consistently 2 to 3 times higher than wheat on the conventional farm. Glasshouse and field trials indicated that the lower colonisation levels on the conventional farm were due to continual use of fertiliser containing solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 19 publications
6
65
0
2
Order By: Relevance
“…1) Field survey of wheat soils predicted that AMF would have the ability to colonize wheat roots at early stages of crop development [35] [36]. The positive effect of R. irregularis inoculation on wheat development is in accordance with previous studies where it has been shown that this fungal isolate was very efficient on the growth of other plant species in controlled conditions [31] [37] [38] and in field conditions [13].…”
Section: Discussionsupporting
confidence: 83%
“…1) Field survey of wheat soils predicted that AMF would have the ability to colonize wheat roots at early stages of crop development [35] [36]. The positive effect of R. irregularis inoculation on wheat development is in accordance with previous studies where it has been shown that this fungal isolate was very efficient on the growth of other plant species in controlled conditions [31] [37] [38] and in field conditions [13].…”
Section: Discussionsupporting
confidence: 83%
“…The importance of AMF pathway in assimilating P for host plants could be decreased when soil P availability is high, which is universally accompanied with a decline in AM colonization (Smith and Smith, 2011). Several evidences have proved that the extractable soil P concentration increases with a reduction in the percentage of root length colonized by AMF (Jensen and Jakobsen, 1980;Ryan et al, 1994;Kahiluoto et al, 2001). However, we did not find a significant effect of P fertilization on the AMF phylotypes and species compositions.…”
Section: Effects Of Fertilization On Amf Abundance and Community Strumentioning
confidence: 99%
“…Especially chlorinated pesticides have had negative impacts on microbial diversity (Mas et al, 1996). Although some authors found no differences in soil microbial diversity between organically and conventionally managed soils (Lawlor et al, 2000;Franke-Snyder et al, 2001), most researchers reported a higher biological diversity for organically than for conventionally managed soils with respect to various taxa, namely bacteria (Sivapalan et al, 1993;Drinkwater et al, 1995;Ma¨der et al, 2002;van Diepeningen et al, 2005), arbuscular mycorrhizal fungi (Ryan et al, 1994;Oehl et al, 2003), nematodes (Mulder et al, 2003;van Diepeningen et al, 2005), earthworms (Ma¨der et al, 2002), and arthropods (Drinkwater et al, 1995;Ma¨der et al, 2002). Also, a higher microbial activity (Workneh et al, 1993;Ma¨der et al, 2002) and microbial biomass (Workneh and van Bruggen, 1994;Ma¨der et al, 2002;Mulder et al, 2003) were found in organically managed soils.…”
Section: Soil Health and Disease Suppressionmentioning
confidence: 99%
“…Regular addition of fairly stable organic matter, including solid animal manure, composts of plant and animal origin, and lignified roots of deep-rooted plants such as alfalfa, rye or grass-clover would enhance microbial biomass, activity, and diversity, and food web complexity in soil (Sivapalan et al, 1993;Ryan et al, 1994;Workneh and van Bruggen 1994;Ma¨der et al, 2002;Schjønning et al, 2002;van Diepeningen et al, 2005). It would also enhance suppression of many soil-borne pathogens (van Bruggen, 1995;van Bruggen and Termorshuizen, 2003).…”
Section: Organic Matter Managementmentioning
confidence: 99%
See 1 more Smart Citation